Experimental and theoretical investigation of the IR spectra and thermochemistry of four isomers of 2-N,N-dimethylaminecyclohexyl 1-N’,N’-dimethylcarbamate - Jalbout, Abraham F.; Li, Xin-Hua; Trzaskowski, Bartosz; Raissi, ‪Heidar (Eclética Química, 2006)
A combined experimental and Density functional theory (DFT) B3LYP/6-311+G* study on the IR spectra of four stable isomers of 2-N,N-dimethylaminecyclohexyl 1-N’,N’-dimethylcarbamate was performed. Our theoretical calculations reveal that two new isomers of this compound exist and may be more stable than the known isomers. In addition the entropy, heat capacity, and the enthalpy content of the stable isomers are computed by fitting the calculated data to a standard Shomate equa- tion and IR spectra for the two new isomers are presented.